1964
DOI: 10.1002/pol.1964.100020507
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular hydride shift polymerization by cationic mechanism. II. Spectroscopic analysis of poly‐3‐methylbutene‐1

Abstract: The structures of cationically obtained poly‐3‐methylbutene‐1, isotactic poly‐3‐methylbutene‐, and hydrogenated 3,4‐polyisoprene have been investigated by nuclear magnetic resonance and infrared spectroscopy. These studies corroborate the previously proposed structure of an α,α′‐dimethylpropane repeating unit for the cationic polymer and they confirm the conventional 1,2 head‐to‐tail enchainment for the isotactic polymer and for the hydrogenated 3,4‐polyisoprene. The NMR spectra of cationic poly‐3‐methylbutene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1964
1964
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[24][25][26][27][28][29][30] Instead of yielding the expected product of olefin polymerization (polyethylene with an isopropyl group on every other carbon), the polymerization proceeded via a 2,3-type hydride shift to form a tertiary carbocation during each propagation step, yielding a gemdimethyl on every third carbon. They reported that if the Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[24][25][26][27][28][29][30] Instead of yielding the expected product of olefin polymerization (polyethylene with an isopropyl group on every other carbon), the polymerization proceeded via a 2,3-type hydride shift to form a tertiary carbocation during each propagation step, yielding a gemdimethyl on every third carbon. They reported that if the Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[27] This was most likely due to the presence of non-hydrogen-shifted repeat units in the polymer, although the NMR techniques of the day were not resolved enough to determine the specific content of the two repeat units in the polymer samples. [30] However, when the polymerization was conducted at À130 8C, the polymer was exclusively hydrogen shifted and consequently was 25-30% crystalline. This semicrystalline polymer exhibited a viscosity average molecular weight of approximately 50 000 g Á mol À1 with a T m of %55 8C and a T g of À12 8C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations